Protective effect of vaginal resveratrol administration on joint tissues in ovariectomized rats: Targeting mTOR and сaspase 3 - Zaychenko, G.; Belenichev, I. F.; Hnatiuk, V.; Doroshenko, A.; Sinitsyna, O.; Sulaieva, O.; Falalyeyeva, T.; Kobyliak, N.; Бєленічев, Ігор Федорович; Дорошенко, А. (My University, 2023)
Introduction: Estrogens play a considerable role in maintaining bone and articular cartilage homeostasis. Menopause provokes joint disorders due to metabolic syndrome and altered signaling pathways. Phytoestrogen resveratrol was demonstrated to provide chondroprotective and osteoprotective effects. However, the mechanisms of such action of Resveratrol are still being explored. Aim: The study aims to determine the effect of Resveratrol on the joints and its therapeutic mechanism in ovariectomized rats. Material and methods: The study was carried out on Wistar female rats that were divided into three groups, including control animals; ovariectomized rats (OVX); and the OVX group treated with an intravaginal gel containing Resveratrol (0.5 % 0.1 mL, daily 28 days). Knee joint tissues (articular cartilage, subchondral plate, subchondral bone) were assessed by histomorphometry. The expression of mTOR, PTEN, Caspase 3 and BCL-2 in articular cartilage and subchondral bone were evaluated immunohistochemically. Results: Resveratrol treatment of OVX rats prevented weight gain by 17 % (P < 0.001), demonstrating the systemic effect on metabolic pathways. Although there were no statistically significant differences in the thickness of articular cartilage between groups, OVX rats possessed degenerative changes in chondrocytes, associated with the enhanced expression of mTOR (P < 0.001) and Casp-3 (P = 0.005). Resveratrol decreased mTOR (P = 0.007) and Casp-3 (P = 0.011) expression in chondrocytes, reducing degenerative changes. At the same time, resveratrol attenuated the deterioration of trabecular bone in OVX rats (P = 0.002). This effect was through the upregulation of BCL-2 (P = 0.018) and down-regulation of Casp-3 expression (P < 0.001). Conclusions: Intravaginal administration of resveratrol provided systemic effects and ameliorated joint tissue structure and signaling in OVX rats through stimulation of BCL-2 and reduced Casp-3 expression.
Keywords: Resveratrol; Polyphenols; Hyaluronic acid; Menopause; Joint tissues; Osteoporosis; Vaginal gel